Periodic Atomic Quasiinterpolation - Basarab, M. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider the approximation of periodic functions by using the atomic quasiinterpolation of the second and the first order. We obtain expressions for the coefficients of quasiinterpolants and present estimates for errors in the uniform metric.